The Effect of Dividends on the Market Share Price: An Applied Study on Jordanian Islamic Financial Companies for the 2010-2018 - Al-Ali, Shireen Mahmoud (International Journal of Economics and Financial Issues, 2020)
The study seeks to show the effect of dividend distributions on the market share price of Jordanian Islamic financial companies for the period 2010-2018, as represented by (Jordan Islamic Bank, Arab International Islamic Bank, Al-Safwa Islamic Bank, First Insurance, Islamic Insurance Company). The study examined the effect of cash and profits dividends and dividends in the form of shares on the market share price of Jordanian Islamic financial companies, also it examined the effect of retained earnings on the market share price of Jordanian Islamic financial companies, which showed that there was no effect of cash distributions on the market share price of financial companies Islamic, and the study also concluded that there is an effect of dividends in the form of shares and retained earnings on the market share price of Jordanian Islamic financial companies. The study recommended that Jordanian Islamic financial companies give great importance to dividing profits between profits distributed among shareholders and retained earnings, as it is one of the factors affecting the market share price of Jordanian Islamic financial companies, since the share price is an effective indicator for investors in making their investment decisions, and shareholders must understand the company’s decision of not distributing the retained profits and detaining them does not mean a negative decision, but rather that it took for them to reuse them in new and diversified investments, which reflects positively on the share price, thus returning to the investor with a double return. Keywords: cash dividend, dividend in the form of shares, retained earnings, market share price JEL Classifications: G1, G2 DOI: https://doi.org/10.32479/ijefi.9389